Rubicon promotes rather than restricts murine lupus and is not required for LC3-associated phagocytosis - Rachael A. Gordon; Christina Giannouli; Chirag Raparia; Sheldon I. Bastacky; Anthony Marinov; William Hawse; Richard Cattley; Jeremy S. Tilstra; Allison M. Campbell; Kevin M. Nickerson; Anne Davidson; Mark J. Shlomchik (JCI Insight, 2022)
NADPH oxidase deficiency exacerbates lupus in murine models and patients, but the mechanisms remain unknown. It is hypothesized that NADPH oxidase suppresses autoimmunity by facilitating dead cell clearance via LC3-associated phagocytosis (LAP). The absence of LAP reportedly causes an autoinflammatory syndrome in aged, nonautoimmune mice. Prior work implicated cytochrome b-245, β polypeptide (CYBB), a component of the NADPH oxidase complex, and the RUN and cysteine-rich domain-containing Beclin 1–interacting protein (RUBICON) as requisite for LAP. To test the hypothesis that NADPH oxidase deficiency exacerbates lupus via a defect in LAP, we deleted Rubicon in the B6.Sle1.Yaa and MRL.Faslpr lupus mouse models. Under this hypothesis, RUBICON deficiency should phenocopy NADPH oxidase deficiency, as both work in the same pathway. However, we observed the opposite — RUBICON deficiency resulted in reduced mortality, renal disease, and autoantibody titers to RNA-associated autoantigens. Given that our data contradict the published role for LAP in autoimmunity, we assessed whether CYBB and RUBICON are requisite for LAP. We found that LAP is not dependent on either of these 2 pathways. To our knowledge, our data reveal RUBICON as a novel regulator of SLE, possibly by a B cell–intrinsic mechanism, but do not support a role for LAP in lupus.